Certified Ethical Hacker (CEH) Version 10 Cert Guide - Gregg, Michael; Santos, Omar (Pearson IT Certification, 2019)
In this best-of-breed study guide, leading experts Michael Gregg and Omar Santos help you master all the topics you need to know to succeed on your Certified Ethical Hacker Version 10 exam and advance your career in IT security. The authors' concise, focused approach explains every exam objective from a real-world perspective, helping you quickly identify weaknesses and retain everything you need to know. Every feature of this book supports both efficient exam preparation and long-term mastery: · Opening Topics Lists identify the topics you need to learn in each chapter and list EC-Council's official exam objectives · Key Topics figures, tables, and lists call attention to the information that's most crucial for exam success · Exam Preparation Tasks enable you to review key topics, define key terms, work through scenarios, and answer review questions ... going beyond mere facts to master the concepts that are crucial to passing the exam and enhancing your career · Key Terms are listed in each chapter and defined in a complete glossary, explaining all the field's essential terminology This study guide helps you master all the topics on the latest CEH exam, including · Ethical hacking basics · Technical foundations of hacking · Footprinting and scanning · Enumeration and system hacking · Social engineering, malware threats, and vulnerability analysis · Sniffers, session hijacking, and denial of service · Web server hacking, web applications, and database attacks · Wireless technologies, mobile security, and mobile attacks · IDS, firewalls, and honeypots · Cryptographic attacks and defenses · Cloud computing, IoT, and botnets.
Online resource; Title from title page (viewed August 9, 2019)
Keywords: Penetration testing (Computer security) -- Study guides -- Examinations; Electronic data processing personnel -- Study guides -- Certification; Computer security -- Study guides -- Examinations; Tests d'intrusion; Examens; Guides de l'étudiant; Sécurité informatique; Examens; Guides de l'étudiant; Computer security; Examinations; Electronic data processing personnel; Certification; examination study guides; Study guides; Guides de l'étudiant